Apelin inhibits the development of diabetic nephropathy by regulating histone acetylation in Akita mouse. (13th December 2013) - Chen, Hong; Li, Jianshuang; Jiao, Lihua; Petersen, Robert B.; Li, Jiong; Peng, Anlin; Zheng, Ling; Huang, Kun
Abstract : Key points: Diabetic nephropathy (DN) is a major complication of diabetes, key features of which include glomerular mesangial expansion, hypertrophy, renal inflammation and accumulation of extracellular matrix proteins in the kidney. Histone acetylation plays an important role in the regulation of inflammation in DN. We found that apelin‐13, the most active member of the adipokine apelin group, decreased glomerular filtration rate, proteinuria, glomerular hypertrophy and mesangial expansion, down‐regulated histone acetylation and suppressed renal inflammation in Akita mouse, a spontaneous DN mouse model. In mesangial cell lines, apelin‐13 treatment not only inhibited high glucose‐induced histone hyperacetylation and inflammation factors, but also up‐regulated histone deacetylase 1. These results revealed the possible mechanisms underlying the regulation of histone acetylation in DN and provide novel approaches to explore the beneficial effects of apelin‐13 on DN. Abstract: Diabetic nephropathy is the primary cause of end‐stage renal disease. Increasing numbers of patients are suffering from this disease and therefore novel medications and therapeutic approaches are urgently needed. Here, we investigated whether apelin‐13, the most active member of the adipokine apelin group, could effectively suppress the development of nephropathy in Akita mouse, a spontaneous type 1 diabetic model. Apelin‐13 treatment decreased diabetes‐induced glomerular filtration rate, proteinuria, glomerular hypertrophy, mesangial expansion and renal inflammation. The inflammatory factors, activation of NF‐κB, histone acetylation and the enzymes involved in histone acetylation were further examined in diabetic kidneys and high glucose‐ or sodium butyrate‐treated mesangial cells in the presence or absence of apelin‐13. Apelin‐13 treatment inhibited diabetes‐, high glucose‐ and NaB‐induced elevation of inflammatory factors, and histone hyperacetylation by upregulation of histone deacetylase 1. Furthermore, overexpression of apelin in mesangial cells induced histone deacetylation under high glucose condition. Thus, apelin‐13 may be a novel therapeutic candidate for treatment of diabetic nephropathy via regulation of histone acetylation.